2018
DOI: 10.21010/ajid.v12i1s.19
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of McE1a Gene From Mycobacterium Tuberculosis Beijing and H37rv Strain for Vaccine Candidate Development

Abstract: Background: Tuberculosis remains the leading cause of death in the world, especially wherever poverty, malnutrition and poor housing prevail. Mycobacterium tuberculosis Beijing strain is the most common strain that causes tuberculosis in Indonesia. The wide spread of tuberculosis has been further aggravated by HIV-AIDS and drug resistance. Unfortunately, Bacille Calmette-Guerin (BCG) as the current vaccine has different protection function and efficacy. According to function analysis, mce1A gene was predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The key to both vaccines lies in the selection of antigen, but DNA vaccine focuses on antigen gene. For example, Mce1A gene may be involved in the invasion and survival of Mtb in human macrophages ( 151 , 152 ). It is suggested that the selection of antigen genes should start from the pathogenesis of tuberculosis and block the pathogenic pathway of Mtb.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…The key to both vaccines lies in the selection of antigen, but DNA vaccine focuses on antigen gene. For example, Mce1A gene may be involved in the invasion and survival of Mtb in human macrophages ( 151 , 152 ). It is suggested that the selection of antigen genes should start from the pathogenesis of tuberculosis and block the pathogenic pathway of Mtb.…”
Section: Dna Vaccinesmentioning
confidence: 99%